Effective organization of lectures through the NEARPOD platform in the formation of linguoculturological competence of pre-service foreign language specialists (Journal of Educational Sciences, 2023)
This research investigates the effectiveness of organizing lectures through the Nearpod platform to enhance the development of linguoculturological competence among pre-service foreign language specialists. It explores how integrating Nearpod's interactive features and authentic cultural content can foster cultural sensitivity, intercultural communication skills, and linguistic awareness in language education. A comprehensive literature review was conducted using multiple databases, including Google Scholar, ERIC, Scopus, Academic Search, EBSCO, and JSTOR. The literature review results from 15 articles indicate that Nearpod has emerged as an effective tool in language education, offering interactive features and authentic cultural content that enhance student engagement and promote effective learning experiences. The utilization of Nearpod has shown promising results in developing linguoculturological competence among pre-service foreign language specialists, fostering cultural sensitivity, intercultural communication skills, and linguistic awareness. The findings suggest that the effective organization of lectures through the Nearpod platform can contribute significantly to the formation of linguoculturological competence. The integration of interactive presentations, formative assessments, and real-time feedback in language instruction enhances student engagement, promotes peer collaboration, and fosters deeper understanding of cultural diversity. By leveraging Nearpod, educators can create dynamic and interactive learning environments that prepare pre-service language specialists for effective intercultural communication in a globalized world.Key words: Nearpod platform, linguoculturological competence, pre-service foreign language specialists, effective teaching methods, intercultural communication, cultural competence, technology integration in education.